2011
DOI: 10.1159/000332225
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Carcinoma Metastatic to the Male Breast after 7 Years: Case Report

Abstract: Background: Colorectal cancer metastasis to a mammary location is very rare. Case Report: A 38-year-old male, who had undergone anterior resection of an advanced rectal carcinoma 7 years earlier, presented with a right mammary mass. Core needle biopsy of the mass indicated cytology consistent with breast adenocarcinoma. After neoadjuvant chemotherapy and modified radical mastectomy, pathology identified the mass as rectal carcinoma. Conclusion: The authors highlight the difficulty of making an accurate diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Compared to the liver or lung metastases, rectal cancer breast metastasis (RCBM), let alone vulvar metastasis, is rather uncommon in existing literature (17)(18)(19). Except 2 male patients, RCBM mainly involved the female in previous reports (20,21). The rareness of this entity might be ascribed to its hormone status and the relatively poor blood supply of a large amount of fibrous tissue, especially in Eastern female (22,23).…”
Section: Discussionmentioning
confidence: 95%
“…Compared to the liver or lung metastases, rectal cancer breast metastasis (RCBM), let alone vulvar metastasis, is rather uncommon in existing literature (17)(18)(19). Except 2 male patients, RCBM mainly involved the female in previous reports (20,21). The rareness of this entity might be ascribed to its hormone status and the relatively poor blood supply of a large amount of fibrous tissue, especially in Eastern female (22,23).…”
Section: Discussionmentioning
confidence: 95%
“…Skin changes such as redness and swelling may also be present, but these can also be seen in advanced breast cancer. Diagnosis based on clinical manifestations alone is difficult ( 7 9 ). Unfortunately, patients with breast metastases from rectal cancer do not show any specific imaging characteristics, and previous literature reports have shown that a significant number of patients are misdiagnosed with primary breast cancer or benign breast diseases based on imaging alone ( 10 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…The response to this regimen was poor, so the NAC was changed to vinorelbine. Following the last round of vinorelbine, modified radical mastectomy and dermoplasty were performed ( 12 ). Gur et al presented a similar case.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is speculated that this may be the route for breast metastasis. Further studies might shed more light on this unorthodox hypothesis (3,4,(11)(12)(13)(14)(15)(16)(17) (Table 3).…”
Section: The Routes Of Breast Metastases Secondary To Rectal Cancermentioning
confidence: 99%